2014
DOI: 10.18632/oncotarget.2480
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of single disseminated prostate cancer cells reveals tumor cell heterogeneity and identifies dormancy associated pathways

Abstract: Cancer dormancy refers to the prolonged clinical disease-free time between removal of the primary tumor and recurrence, which is common in prostate cancer (PCa), breast cancer, esophageal cancer, and other cancers. PCa disseminated tumor cells (DTC) are detected in both patients with no evidence of disease (NED) and advanced disease (ADV). However, the molecular and cellular nature of DTC is unknown. We performed a first-in-field study of single DTC transcriptomic analyses in cancer patients to identify a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 30 publications
3
105
0
Order By: Relevance
“…Culture of PCa cells with NE demonstrated a decrease in expression of both p27 and p21 (Figure 3A–C). Previous reports have demonstrated that an increased ratio of p-ERK 1/2 to p-p38 MAPK is associated with re-activation from dormancy in prostate and other cancers (7,9,31). Thus, we also evaluated p-ERK and p-p38 levels following exposure to NE (Figure 3D–E).…”
Section: Resultsmentioning
confidence: 95%
“…Culture of PCa cells with NE demonstrated a decrease in expression of both p27 and p21 (Figure 3A–C). Previous reports have demonstrated that an increased ratio of p-ERK 1/2 to p-p38 MAPK is associated with re-activation from dormancy in prostate and other cancers (7,9,31). Thus, we also evaluated p-ERK and p-p38 levels following exposure to NE (Figure 3D–E).…”
Section: Resultsmentioning
confidence: 95%
“…Hypoxia activates an unfolded protein response (UPR) that results in the attenuation of translation initiation and the induction of cell cycle arrest genes [4,109,110]. Intriguingly, the UPR was found in dormant cancer cells in experimental models [111] and transcripts for speci c UPR genes were also found to be upregulated in dormant DTCs isolated from BM of prostate cancer patients [112]. These genes could also be turned on in DTCs in the target organ by the fact that they carry a signature epigenetically imprinted in the primary tumors (i.e., the DTCs carry a remodeled chromatin in response to hypoxia in the primary site) [7,113].…”
Section: Routes By Which Hypoxia Affects Dtc Fatementioning
confidence: 99%
“…The culprits for the recurrent disease are the small number of residual cells that are disseminated from the primary tumor prior to treatment (4). Even patients with asymptomatic disease or no evidence of primary disease progression are known to often harbor cancer cells at distant organs such as bone, and they can be isolated from the bone marrow aspirate (5). These cells include quiescent cancer stem cells (CSCs) 2 and may reacquire clonogenic growth in a favorable environment and cause recurrent disease, which is evident in 20 -50% of patients who were treated for localized primary disease (6).…”
mentioning
confidence: 99%